The Effect Of Islamic Financing On Bank Performance: Evidence From Indonesian Islamic Banks - Nuril Islah; Nasihuddin; Rabi'atul Adawiyah (CV. SINAR HOWUHOWU, 2026)
This study examines the effect of Islamic financing on the performance of Islamic banks in Indonesia. The research focuses on three main financing instruments, namely murabaha, mudaraba, and musharaka, and their influence on bank profitability as measured by Return on Assets (ROA). Using a quantitative approach with an explanatory research design, this study analyzes secondary data obtained from the financial statements of Islamic commercial banks over a specified observation period. The data are processed using multiple linear regression analysis to evaluate both partial and simultaneous effects of the independent variables on bank performance. The results show that murabaha financing has a positive and significant effect on ROA, indicating that trade-based financing plays a dominant role in enhancing bank profitability. Similarly, musharaka financing also demonstrates a positive and significant influence, suggesting that partnership-based contracts can contribute to improved financial performance when managed effectively. In contrast, mudaraba financing shows a positive but statistically insignificant effect, reflecting the challenges associated with profit-sharing schemes, such as higher risk and information asymmetry. Overall, the findings highlight that while Islamic banking principles emphasize profit-and-loss sharing, in practice, bank performance is still largely driven by less risky financing instruments. This study provides empirical evidence that contributes to the existing literature on Islamic banking and offers practical insights for policymakers and financial institutions in optimizing financing structures to achieve both profitability and Sharia compliance.